1987
DOI: 10.1159/000124879
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide Hydrolysis in Response to the Withdrawal of Dopamine Inhibition in Enriched Lactotrophs in Culture

Abstract: The formation of inositol phosphates and hydrolysis of polyphosphoinositides in response to DA addition or removal was studied in cultured anterior pituitary cells from E2-treated rats. The cells were incubated for 24 h with [3H]inositol to label the polyphosphoinositides either with or without DA (500 nM) in the medium. [3H]inositol phosphate and [3H]polyphosphoinositide levels were determined by anion-exchange chromatography after KOH deacylation of the latter. Acute (5 min) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

1989
1989
1995
1995

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…(20) have indicated that the PI cycle may be the intracellular mechanism through which PRL release is inhibited by DA. Furthermore, it has been suggested that the PI messenger system of lactotrophs is negatively coupled to DA receptors (21). Our studies were performed concomitantly with cells obtained from an estrone-induced pituitary adenoma and two pituitary tumors in order to try and better understand the role of PI in the control of PRL release.…”
Section: Discussionmentioning
confidence: 99%
“…(20) have indicated that the PI cycle may be the intracellular mechanism through which PRL release is inhibited by DA. Furthermore, it has been suggested that the PI messenger system of lactotrophs is negatively coupled to DA receptors (21). Our studies were performed concomitantly with cells obtained from an estrone-induced pituitary adenoma and two pituitary tumors in order to try and better understand the role of PI in the control of PRL release.…”
Section: Discussionmentioning
confidence: 99%
“…PKC activated by phorbol esters enhances adenylate cyclase activity by inhibiting the inhibitory activity of GTP-binding Gj-protein. TRH also stimulates the cyclase activity by stimulat ing GTP-binding Gs-protein [16], It was also suggested that dopaminergic D2 receptors may be linked to the phospholipase C system by demonstrating that a brief ex posure to dopamine enhanced phosphatidyl inositol bi phosphate [17], Another group of workers proposed that the D2 receptors may be negatively coupled to the phos pholipase C system [18][19][20], but it has been difficult to demonstrate an inhibitory effect of dopamine on total inositol phosphate production [21].…”
Section: Inmentioning
confidence: 99%
“…Acute withdrawal of D A activates adenylate cyclase [ 15], phospholipase C [ 12,15], and protein kinase C [18] in dispersed anterior pituitary cells from E2-treated rats. Pretreatment of the cells with cyclic A M P ana logues or with direct activators o f adenylate cyclase resulted in potentiation o f the action o fT R H mimicking the effect o f tran sient D A withdrawal [14], In agreement with these results, pre treatment with V IP also potentiated the action o fT R H [14], Since V IP is a known activator o f adenylate cyclase in lactotrophs, these results suggested a role for adenylate cyclase med iating the action o f D A withdrawal to potentiate the action of T R H .…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the effect o f transiently turning o ff D A on TRH effectiveness could be mimicked by pharmacologically in creasing cellular levels o f cyclic A M P or activating protein ki nase C with TPA [14]. Removal o f D A was shown to be an effec tive signal in enriched lactotrophs for the activation of adenylate cyclase [15], phospholipase C [ 12,15] and protein kinase C [ 18]-PRL has been shown to be contained within multiple functional pools within lactotrophs depending on elapsed time since its synthesis [19][20][21]24]. We reasoned that the ability o f D A with drawal to directly release PRL or potentiate the releasing action o f T R H could be accomplished through different functional pools o f PR L, i.e., the direct effect could be mediated through the release o f PRL o f different ages than the potentiating action.…”
mentioning
confidence: 90%